Bung: A traditional practice of potato cultivation in eastern hills of Nepal - Upadhyay, Kalika Prasad; Timilsina, Amit Prasad (Journal of Agriculture and Natural Resources, 2020)
Eastern hill region is one of the high potato producing areas of potato in Nepal. There are many traditional potato production systems existing in the region. Among them, 'Bung' and 'Lhose' are very popular systems. There are some under-proven views of naming to this unique cultivation practice. Field observations, key informants' interview, and group discussion were carried out at three sites of Okhaldhunga and Solukhumbu districts in July 2019 to explore the basic information on the bung system. The results of this investigation revealed that the century-old practice utilized marginal sloppy lands of mountains for cultivation of potatoes. Farmers left land fallow for 4-5 years to grow weeds and herbs. Thereafter, they slashed them with a thin layer of soil, stacked them over winter, burned and mixed with the soil making a raised pit. They planted 15-25 potato seed tubers into these pits depending upon the pit size. No additional fertilizer is added to these pits. No intercultural operations are carried out until harvesting. It was explained that the yield of potato from the bung was significantly higher 15-20 kg) than that of general local practice called lhose system (5-7 kg) from the area equivalent to Bung . Some interventions such as high yielding varieties, easy-to-handle equipment for bung preparation and introduction of fast-growing non-hazardous weeds, etc. were the demands of the farmers to increase profit from the bung system.